shRNAs targeting mouse Adam10 diminish cell response to proinflammatory stimuli independently of Adam10 silencing - Maria Czarnek; Krystyna Stalińska; Katarzyna Sarad; Joanna Bereta (Biology Open, 2022)
RNA interference is one of the common methods of studying protein functions. In recent years critical reports have emerged indicating that off-target effects may have a much greater impact on RNAi-based analysis than previously assumed. We studied the influence of Adam10 and Adam17 silencing on MC38CEA cell response to proinflammatory stimuli. Eight lentiviral vector-encoded shRNAs that reduced ADAM10 expression, including two that are specific towards ADAM17, caused inhibition of cytokine-induced Nos2 expression presumably via off-target effects. ADAM10 silencing was not responsible for this effect because: (i) CRISPR/Cas9 knockdown of ADAM10 did not affect Nos2 levels; (ii) ADAM10 inhibitor increased rather than decreased Nos2 expression; (iii) overexpression of ADAM10 in the cells with shRNA-silenced Adam10 did not reverse the effect induced by shRNA; (iv) shRNA targeting ADAM10 resulted in decrease of Nos2 expression even in ADAM10-deficient cells. The studied shRNAs influenced transcription of Nos2 rather than stability of Nos2 mRNA. They also affected stimulation of Ccl2 and Ccl7 expression. Additionally, we used vectors with doxycycline-inducible expression of chosen shRNAs and observed reduced activation of NF-κB and, to a lesser extent, AP-1 transcription factors. We discuss the requirements of strict controls and verification of results with complementary methods for reliable conclusions of shRNA-based experiments.